Comparison of the Expression of Acetylated Histones H3 and H4 and the Deacetylase Enzymes HDACs 1, 2, and 6 in Neoplastic and Nonneoplastic Canine Mammary Tissues - Igor Luiz Salardani Senhorello; Oscar Rodrigo Sierra Matiz; Isabela Cristina Canavari; Giovanni Vargas-Hernandez; Letícia Abrahão Anai; Roberto Andrés Navarrete Ampuero; Josiane Moraes Pazzini; Cibele Maria Prado; Flávio Vieira Meirelles; Rosemeri de Oliveira Vasconcelos; Mirela Tinucci-Costa (Veterinary Medicine International)
Epigenetic alterations play a crucial role in the pathogenesis of cancer, as changes in the expression of DNA-associated proteins can affect gene expression. However, these changes may be reversible following treatment. This study aimed to evaluate the expression of acetylated histones H3 and H4 and the deacetylase enzymes HDACs 1, 2, and 6 in canine mammary tissues in order to identify potential alterations due to aberrant protein expression in neoplastic tissues. For this purpose, mammary tissue samples from 91 canine patients were divided into four groups: G1, control group composed of mammary tissues with no histopathological changes (n = 11); G2, simple mammary adenomas (n = 19); G3, simple mammary carcinomas without metastasis (n = 46); and G4, simple mammary carcinomas with lymph node metastasis (n = 15). The tissues were subjected to immunohistochemical analysis to assess protein expression. Antibody validation was performed by Western blot. The antibody expression results were evaluated semiquantitatively, considering the staining intensity and the percentage of marked cells. Univariate and multivariate analyses with a 5% significance level revealed differences in the expression of acetylated histones and deacetylase enzymes among the experimental groups (p<0.05). Reduced acetylation of H3 (H3K9Ac) was observed in both nonmetastatic and metastatic simple mammary carcinomas compared to normal mammary tissue. Additionally, lower expression of HDAC1 and HDAC2 was found in neoplastic mammary tissues compared to normal tissue (p<0.05). Conversely, HDAC6 exhibited higher expression in neoplastic mammary tissues (p<0.05). There was no difference in the expression of acetylated H4 (H4K12Ac) among the groups (p > 0.05). Multivariate analysis showed a positive association between the expression of HDAC1 and HDAC2 and a negative association between H3K9Ac and HDAC6. These associations highlighted aberrant expression in mammary carcinomas compared to normal mammary tissues, indicating that epigenetic alterations exist in canine mammary neoplasms and that high HDAC6 expression may explain the observed hypoacetylation of H3 in neoplastic tissues. Collectively, these findings suggest that such alterations could potentially be therapeutic targets for the treatment of mammary cancer in dogs.